COMMUNITY PERSPECTIVE ON FOREST CONDITION (CASE STUDY IN KTH TALANG PONIJAN AND SIDODADI I) - Elsa Nadia Almaidah; Iswandaru, Dian; Kaskoyo, Hari; Wulandari, Christine; Darmawan, Arief; Rahma Fitriana, Yulia; Safe'i, Rahmat; Herwanti, Susni; Novriyanti, Novriyanti; Gumay Febryano, Indra (Forestry Study Program University Of Mataram, 2025)
The sustainability of forest functions is closely related to the perspective of the communities living around it. This study aims to analyze community perspectives on forest conditions in KTH Talang Ponijan and Sidodadi I. Data was collected using a qualitative approach through in-depth interviews, participant observation, and documentation studies. The collected data were analyzed descriptively and qualitatively. The results of the research show that there are still differences between the community's views and their behavior towards community forest management (HKm). Most people in KTH Talang Ponijan and Sidodadi I utilize HKm land to improve their welfare. However, conditions in the field reveal that illegal practices such as logging, poaching, opening up new land for cultivation, and unsustainable land management threaten the balance of nature and worsen forest conditions. The government is expected to provide environmental education programs and facilitate training or guidance to strengthen the community's capacity to manage and utilize forests wisely.